Pengembangan Arsitektur Model Proses Bisnis Sekolah - Huda, Nuzulul; Ningrum, Eka Cahya; Tsaqif, Hilmi; Yaqin, Muhammad Ainul (STIKOM Tunas Bangsa Pematangsiantar, 2020)
Determination of school business processes is very important in order to achieve the vision, mission, and goals of the school that has been determined, but many schools that run business processes do not follow the standards set by the national education standards body. Therefore there is a need for a business process that is in line with national education standards. The final results obtained from this study are in the form of architectural business process models from schools using the Togaf ADM method that can be used as a reference in conducting every business process in school.